Effects of fatigue on shooting performance and biomechanical patterns in elite biathletes - Sattlecker, G.; Buchecker, M.; Birklbauer, J.; Müller, E.; Lindinger, S. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The aim of the current study was to analyze biomechanical shooting patterns and performance issues in elite biathletes under simulated race conditions. Specific aims were to investigate the differences in dependent variables for prone and standing shooting between 1) rest vs. load situation and 2) high vs. low performers. Based on previous studies fatigue was expected to affect biomechanical patterns which are considered to be more efficient in biathletes with higher scores.